The Problem of Preparing Future Designers - A. Prishchepa, A.; A. Burovkina, L.; V. Koreshkov, V. (International Journal of Engineering and Technology, 2018)
The article is devoted to the study of professional training of future designers. The concepts of "competence", "professional competence" in the research of specialists are revealed. According to the authors, higher education is not a privilege, not the lot of the elected, but not a set of basic knowledge and skills. The diploma of higher education does not certify the identity or citizenship and not the rights and freedoms of the individual, but only the level of qualification in the specialty that requires fundamental scientific training. The system of higher education, unlike educational organizations, provides citizens with the special knowledge, skills and abilities required to replace well-defined places in the system of social division of labor. There are many professions in demand in the labor market and vital to society, the mastery of which requires training at the University and allows the individual to fully realize their abilities. The creation of a comfortable environment in higher education, helping young people to understand that in the pursuit of self-realization and achievement of success in life should be guided not by the prevailing stereotypes, and their own desires and inclinations, is a necessary condition for the successful professional development of the individual graduate.Â Â Â